2020
DOI: 10.1002/chir.23254
|View full text |Cite
|
Sign up to set email alerts
|

Four cypermethrin isomers induced stereoselective metabolism in H295R cells

Abstract: Cypermethrin (CP) is widely used for controlling agricultural and indoor vermin. Previous studies have reported the stereoselective difference of CP in biological activities. However, little is known about their potential mechanisms between metabolic phenotypes and endocrine‐disrupting effects. Herein, nuclear magnetic resonance (NMR)‐based metabolomics combining metabolite identification and pathway analysis were applied to evaluate the stereoselective metabolic cdisorders induced by CP isomers in human adren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…Studies have shown that cis-isomers of CP exhibit a higher metabolic disruption than the trans-isomers, including disruption of glucose and amino acid metabolism, potentially contributing to metabolic syndrome. 7 Additionally, the cis-isomers possess stronger reproductive toxicity, potentially leading to diminished sperm motility. 37 Therefore, in the risk assessment and toxicological studies of CP exposure from consuming oysters, it is important to consider the difference in absorption rates between cis-and trans-isomers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that cis-isomers of CP exhibit a higher metabolic disruption than the trans-isomers, including disruption of glucose and amino acid metabolism, potentially contributing to metabolic syndrome. 7 Additionally, the cis-isomers possess stronger reproductive toxicity, potentially leading to diminished sperm motility. 37 Therefore, in the risk assessment and toxicological studies of CP exposure from consuming oysters, it is important to consider the difference in absorption rates between cis-and trans-isomers.…”
Section: Discussionmentioning
confidence: 99%
“…In dietary exposure through CP-containing oysters, the cis -isomers of CP might finally accumulate in the body at a higher ratio and further produce toxic effects. Studies have shown that cis -isomers of CP exhibit a higher metabolic disruption than the trans -isomers, including disruption of glucose and amino acid metabolism, potentially contributing to metabolic syndrome . Additionally, the cis -isomers possess stronger reproductive toxicity, potentially leading to diminished sperm motility .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation